AN APPRECIATION OF ART IN MALAYSIA: THE PROBLEMS AND BENEFITS IN SOCIETY - Izani Mat; Md Baharuddin Abdul Rahman; Harleny Abd Arif; Elis Mokhtar (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This paper focuses on the problems and benefits of art in Malaysia. An Appreciation of art is not just appreciation as the meaning of the words, but the appreciation of art includes knowing, recognizing, understanding, and appreciating. Theoritically, these four scopes of appreciations are required to be mastered in order to appreciate an artwork and to make an artistic criticism accurately. The critical issues regarding art scene in Malaysia is categorized into three groups, namely, the group of traditional artwork (artwork whose form and function is still "pure"), the group of modern artwork that has been "adapted" or given "new breath" of traditional art (art traditional that has been combined with modern elements includes either in form or function), and a group of modern works that use the Western approaches (forms of modern works from the West which has been brought into Malaysia). This makes the method of art criticism in Malaysia become exceptional and unique.